Pengaruh Perilaku Memilih Terhadap Penurunan Partisipasi Politik Dalam Pemilihan Walikota dan Wakil Walikota Medan 2015 - Lingga, Andreas Robin; Ali Azhar, Muhammad; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2019)
ABSTRACT Political participation is the activity of a person or group of people in influencing the general policies to be taken by the government. Political participation of the people in North Sumatra has decreased from several elections that occurred. This study aims to determine the effect of voting behavior on decreasing political participation. This study uses data collection techniques with a survey method using a questionnaire as the main instrument. The results of this study note that the influence of voting behavior on the decline in political participation. The most significant factor influencing voting behavior is the religious factor. Keywords: Selecting Behavior, Reducing Political Participation, 2015